2005
DOI: 10.5688/aj690228
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Audience Response System to Introduce an Anticoagulation Guide to Physicians, Pharmacists, and Pharmacy Students

Abstract: Objectives. To implement an anticoagulation guide (AG) and measure understanding with an audience response system (ARS). Secondly, to describe prescribing practices following AG implementation and survey pharmacy students' opinions of the ARS. Methods. Medical and pharmacy residents, pharmacy students, and clinical staff pharmacists responded to 7 case-based multiple-choice questions related to anticoagulation with the ARS before and after an educational intervention. Following AG implementation, a retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 14 publications
3
24
0
Order By: Relevance
“…Our findings support other pharmacy education studies that describe positive student outcomes associated with student engagement [39][40][41][42][43][44][45] and performance [3,40,46,42,43] in ARS based learning. In fact, ARS is one of the most commonly used active learning strategies in US Colleges and Schools of Pharmacy [4].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings support other pharmacy education studies that describe positive student outcomes associated with student engagement [39][40][41][42][43][44][45] and performance [3,40,46,42,43] in ARS based learning. In fact, ARS is one of the most commonly used active learning strategies in US Colleges and Schools of Pharmacy [4].…”
Section: Discussionsupporting
confidence: 90%
“…The majority of the students in our survey also reported that the i-SIDRA system promoted the clarification and understanding of concepts (median: 5). These findings are in agreement with those of other studies which report the ability of ARSs to enhance understanding of the material [46,42].…”
Section: Surveysupporting
confidence: 93%
See 1 more Smart Citation
“…4 Most participants in an anticoagulation guide session agreed that ARS utilization increased their involvement in the presentation and understanding of its content. 5 Students and instructors in a dual-campus environment found that an ARS increased active learning, revealed student comprehension, and helped instructors identify course concepts that students misunderstood. 6 Issues with ARS usage have included faculty members' concerns regarding academic integrity and students' concerns over technical issues that could negatively affect grades.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Three polling questions per 50-minute class session spaced every 15 minutes appeared optimal. Student interest in performing well was also enhanced if points were awarded for correct responses.…”
Section: American Journal Of Pharmaceutical Education 2012; 76 (8) Armentioning
confidence: 99%